2017
DOI: 10.1177/0022034517740577
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Labeling and 2-Photon Imaging of Mouse Tooth Pulp Nociceptors

Abstract: Retrograde fluorescent labeling of dental primary afferent neurons (DPANs) has been described in rats through crystalline fluorescent DiI, while in the mouse, this technique was achieved with only Fluoro-Gold, a neurotoxic fluorescent dye with membrane penetration characteristics superior to the carbocyanine dyes. We reevaluated this technique in the rat with the aim to transfer it to the mouse because comprehensive physiologic studies require access to the mouse as a model organism. Using conventional immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 32 publications
(54 reference statements)
0
14
0
Order By: Relevance
“…Next, we utilized RNAscope technology for a sensitive read-out of RNA levels in the trigeminal ganglion of genes implicated in both nociceptive and inflammatory responses. The trigeminal ganglion was examined as cell bodies of the primary afferent neurons that innervate the dental pulp reside there 16 . We chose to assess the Toll-like Receptor 4 (Tlr4), transient receptor potential channels vanilloid 1 and ankyrin 1 (Trpv1 and Trpa1), and the mas-related G protein coupled receptor D (Mrgprd), because all are found in neurons that innervate the dental pulp 7,[17][18][19][20][21] and could be involved in the development of either spontaneous or mechanical pain in the context of infection and injury.…”
Section: Morphological and Gene Expression Changes Twenty-four Hours mentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we utilized RNAscope technology for a sensitive read-out of RNA levels in the trigeminal ganglion of genes implicated in both nociceptive and inflammatory responses. The trigeminal ganglion was examined as cell bodies of the primary afferent neurons that innervate the dental pulp reside there 16 . We chose to assess the Toll-like Receptor 4 (Tlr4), transient receptor potential channels vanilloid 1 and ankyrin 1 (Trpv1 and Trpa1), and the mas-related G protein coupled receptor D (Mrgprd), because all are found in neurons that innervate the dental pulp 7,[17][18][19][20][21] and could be involved in the development of either spontaneous or mechanical pain in the context of infection and injury.…”
Section: Morphological and Gene Expression Changes Twenty-four Hours mentioning
confidence: 99%
“…Thus, we could not be fully certain that the neurons we visualized in the trigeminal ganglion came from the tooth pulp versus other trigeminal tissues. However, our own preliminary studies and others 16 have shown that maxillary molar labeling with the DiI paste Neurotrace (Invitrogen) results in positive cells in all branches of the trigeminal nerve, therefore we imaged cell clusters observed in both the region where V3 and V2 meet, as well as the region where V1 and V2 meet, resulting in 2 images per section with the 20x objective. As we have previously described 46 all cells with detectable signal were selected for quantification and the signal intensity of mRNA clusters observed within each cell was analyzed by drawing a region of interest around each cell and mean signal intensity in arbitrary units generated by ImageJ software was noted.…”
Section: Scorementioning
confidence: 99%
“…Next, we utilized RNAscope technology for a sensitive read-out of RNA levels in the trigeminal ganglion of genes implicated in both nociceptive and inflammatory responses. The cell bodies of the primary afferent neurons that innervate the dental pulp reside in the trigeminal ganglion 24 . We chose to assess the Toll-like Receptor 4 (Tlr4), transient receptor potential channels vanilloid 1 and ankyrin 1 (Trpv1 and Trpa1), and the mas-related G protein coupled receptor D (Mrgprd), because all are found in neurons that innervate the dental pulp 7,20,22,25-27 and could be involved in the development of either spontaneous or mechanical pain in the context of infection and injury.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we could not be fully certain that the neurons we visualized in the trigeminal ganglion came from the tooth pulp versus other trigeminal tissues. However, our own preliminary studies and others 24 have shown that maxillary molar labeling with the DiI paste Neurotrace (Invitrogen) results in positive cells in all branches of the trigeminal nerve, therefore we imaged cell clusters observed in both the region where V3 and V2 meet, as well as the region where V1 and V2 meet, resulting in 2 images per section with the 20x objective. All cells with detectable signal were selected for quantification and the signal intensity of mRNA clusters observed within each cell was analyzed by drawing a region of interest around each cell and mean signal intensity in arbitrary units generated by ImageJ software was noted.…”
Section: Methodsmentioning
confidence: 99%
“…In the skin, TRPM8 and TRPA1 act synergistically and represent the key sensors of environmental cooling as well as painful cold (5,6). TRPM8 and TRPA1 mRNA and protein are present in high density in the trigeminal ganglion (TG) and in the sensory axons of the tooth pulp (7)(8)(9). In addition, cultured human odontoblast-like cells (10) and cultured dental pulp fibroblasts (11) exhibit cold-induced increases in intracellular calcium in vitro, which is partly explained by their TRPA1 and TRPM8 channels.…”
Section: Introductionmentioning
confidence: 99%